Shaping Ethical Digital Citizens through Islamic Education - Pranoto, Bayu Ady; Haryanto, Budi (Indonesian Journal of Islamic Studies, 2024)
General Background: Education in Indonesia faces complex challenges related to concepts, regulations, and implementation across various educational systems. A critical issue is the development of student character, particularly in the digital era where graduates struggle to remain competitive globally. Specific Background: Islamic education plays a vital role in shaping students' characters, imparting religious values, ethics, and morality. In the digital era, this education extends beyond traditional religious teaching to address ethical and moral use of technology. Knowledge Gap: Despite significant research on Islamic education, little attention has been given to its role in teaching digital ethics and responsible technology use in the context of student character development. Aims: This study aims to investigate how Islamic education can shape students' character in the digital era by promoting moral values, digital ethics, and spiritual awareness. Results: The research shows that Islamic education has a positive impact on the moral and ethical development of students. It integrates religious teachings with digital ethics, fostering responsible behavior and spiritual growth in the use of technology. Novelty: This study highlights the novel role of Islamic education in bridging religious values and digital ethics, providing a holistic approach to student character development in a digitalized world. Implications: The findings suggest a need for curriculum development focused on integrating digital ethics and Islamic values, teacher training in ethical technology use, and collaboration with parents to support character formation in students. This research offers crucial insights for educational institutions aiming to adapt to the challenges of the digital era. Highlights: Islamic education blends moral values and digital ethics for character growth. Teachers need training to teach responsible technology use effectively. Parent collaboration boosts student character in the digital age. Keywords: Islamic education, character development, digital ethics, student behavior, moral values